A hundred years of tiny mortars - Salt, John D. (Cranfield University, 2022)
In 1915, Wilfred (later Sir Wilfred) Stokes serendipitously invented a trench mortar which set the pattern for medium and heavy mortars to this day. Stokes-Brandt mortars are smooth-bored, muzzle-loading, drop-fired weapons, with a system of variable charges (increments), and using the ground to absorb recoil. This presentation covers a rather different class of weapon which arose during the 1920s. These are trigger-fired, 37 to 52mm in calibre, with no charge system, described variously as light mortars, grenade dischargers, or misleadingly as “knee mortars”. A variety of design approaches is described, and evaluated in terms of throw-weight and range. The most efficient and successful designs seem to be the simplest. These tiny mortars were popular before World War 2, especially with Imperial Japan, but by the end of the war most major combatants had lost their enthusiasm for such weapons. Great Britain, unusually, retained a weapon in this class until quite recently. The current state of the art is represented by French and Chinese designs of captive-piston spigot mortar, which have enviable stealth characteristics. The author believes that it is still useful for an infantry platoon to have a light mortar capable of throwing a one-kilogram bomb to half a kilometre.